Efficacy of progesterone supplementation during early pregnancy in cows: a meta-analysis - Yan, Leyan; Robinson, Robert S.; Shi, Zhendan; Mann, George E. (Elsevier, 2016)
Progesterone is a critical hormone during early pregnancy in the cow. As a result, a number of studies have investigated the effects of progesterone supplementation on pregnancy rates. In this study, a meta-analysis using a univariate binary random effects model was carried out on 84 specific treatments reported in 53 publications involving control (n = 9905) and progesterone-treated (n = 9135) cows. Although the results of individual studies showed wide variations (−40% to +50% point changes), progesterone treatment resulted in an overall increase in pregnancy rate odds ratio (OR = 1.12; P < 0.01). Improvements in pregnancy rate were only observed in cows treated at natural estrus (OR = 1.41, P < 0.01) and not following synchronization of estrus or ovulation. Although treatment between Days 3 to 7 postinsemination was beneficial (OR = 1.15; P < 0.01), treatment earlier or later than this was not. Progesterone supplementation was beneficial in cows of lower fertility (<45% control pregnancy rate) but not in cows with higher fertility. These results indicated that the benefit of progesterone supplementation on fertility of cows required exogenous progesterone supplementation to start between Day 3 to 7 and the appropriate reproductive status (i.e., lower fertility, natural estrus) of the treated cows.